Perencanaan Ulang Pondasi Pilar Jembatan Sikabu Kayu Gadang - N Nanda; Maiyozzi Chairi; Nofri Fu’adi Rahmat (Civil Engineering Collaboration, 2021)
The construction of transportation facilities such as bridges plays an important role in the development of human resources today because more and more road users will use these facilities. The Sikabu Kayu Gadang Bridge has a span of 100 meters with a structure of precast concrete, abutments, pillars and a foundation of concrete and steel piles which inspired the authors to conduct research. In this type of selection, several things need to be considered, such as the load being carried and the location of the hard ground. Based on this, this study aims to analyze the deep foundation that can be applied to the project in the hope of getting more efficient results. Based on the re-planning, the bearing capacity of the foundation permit (Qall) is 1254.98 kN with a diameter of 0.5 m and a depth of 20 m. The permitted bearing capacity of the pile group (Qall) is 12795.46 kN to withstand the loads acting on the superstructure. Bore Pile foundation logitudinal reinforcement = 10 D16 and Bore Pile shear reinforcement = ᴓ 12 – 150 mm.